The Influence of Work Environment and Compensation on Employee Performance: The Role of Job Satisfaction as an Intervening Variable: Pengaruh Lingkungan Kerja dan Kompensasi terhadap Kinerja Karyawan: Peran Kepuasan Kerja sebagai Variabel Intervening - Putri, Cantika; Hebel Pertiwi; cantika (Sumatera Scientist, 2026)
Employee performance is an important factor in improving the quality of services in health institutions. The work environment and compensation are considered factors that may influence employee performance either directly or indirectly through job satisfaction. This study aims to analyze the effect of the work environment and compensation on employee performance with job satisfaction as an intervening variable at Barung-Barung Balantai Public Health Center, Pesisir Selatan Regency. This research employed a quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 3.0 as the analytical tool. The population consisted of all employees of the Barung-Barung Balantai Public Health Center totaling 89 employees. The sampling technique used was saturated sampling, resulting in 30 respondents as the research sample. The results show that the work environment does not have a significant effect on job satisfaction, while compensation has a significant effect on job satisfaction. Furthermore, the work environment has a significant effect on employee performance, whereas compensation does not significantly affect employee performance. Job satisfaction also does not significantly influence employee performance. In addition, job satisfaction is not able to mediate the effect of the work environment and compensation on employee performance. These findings indicate that improving employee performance at the Barung-Barung Balantai Public Health Center is more directly influenced by the work environment rather than through job satisfaction as an intervening variable.